NEW FOLIICOLOUS HYPHOMYCETES FROM KATHMANDU VALLEY, NEPAL - and KAMAL, M. K. KHAN, USHA BUDATHOKI (Indian Phytopathology, 2002)
Pseudocercospora myricacearum sp. novo (Euonymis echinatus-Myricaceae), Spiropes stranvaesiae sp. novo (Stranvaesia glaucescens-Rosaceae), Stenella prinsepiae sp. novo (Prinsepia utilis-Rosaceae) and Verrucispora luculiae sp. novo (Luculia gratissima-Rubiaceae) collected from Kathmandu Valley are described illustrated and compared with allied species.